Siloxane electrolyte, preparation method thereof and application of siloxane electrolyte in low-temperature lithium metal battery

By using siloxane electrolyte in lithium metal batteries, combining specific lithium salts and dimethoxydimethylsilane ratios, the problem that existing low-temperature electrolytes are difficult to have multiple characteristics is solved, and the efficient and environmentally friendly electrochemical performance of lithium metal batteries under low temperature conditions is achieved.

CN119742457AActive Publication Date: 2025-04-01XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411939094.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing low-temperature electrolytes are difficult to have both weak solvation, high-voltage resistance, low cost and environmentally friendly characteristics, which limits the high reversible charge and discharge performance of lithium metal batteries under low temperature conditions.

Method used

A siloxane electrolyte, including lithium salt and dimethoxydimethylsilane, is used to control the mass ratio of lithium salt and dimethoxydimethylsilane to form a uniform and transparent solution, achieving good fluidity and high chemical stability under low temperature conditions.

Benefits of technology

It achieves high chemical stability and excellent electrochemical performance of lithium metal batteries under low temperature conditions, is low cost and environmentally friendly, can match the ternary positive electrode and operate stably under 4.7V conditions, and has excellent low-temperature capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742457A_ABST
    Figure CN119742457A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium metal batteries, and particularly relates to a siloxane electrolyte, a preparation method thereof and application of the siloxane electrolyte in a low-temperature lithium metal battery. The siloxane electrolyte is prepared from a lithium salt and dimethoxy dimethyl silane, and the mass ratio of the lithium salt to the dimethoxy dimethyl silane is (0.16 to 0.48) to (0.5 to 1.5). The siloxane electrolyte composition provided by the invention comprises the lithium salt and the dimethoxydimethylsilane, and silicon atoms and adjacent oxygen atoms in the dimethoxydimethylsilane have a d-p conjugation effect, so that the high voltage resistance of the electrolyte is effectively improved, the Li < + >-solvent interaction can be weakened, and the release of lithium ions in the desolventizing process is promoted; by combining a low-temperature formation mode, the electrochemical performance of the lithium battery in a low-temperature interval can be remarkably improved, the lithium battery can be matched with a ternary positive electrode and stably run under the condition of 4.7 V, and the lithium battery has an excellent low-temperature capacity retention rate and has a wide application prospect in the low-temperature lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a siloxane electrolyte and a preparation method thereof and application in low-temperature lithium metal batteries. Background Art

[0002] Lithium-ion batteries with graphite negative electrodes have difficulty achieving high reversible charge and discharge performance at low temperatures, especially below -40°C. Under such working conditions, the lithium insertion potential of graphite is easily reduced to a value relative to Li / Li + When the voltage drops below 0.0V, lithium deposition occurs, which limits the reversibility of lithium-ion batteries. In contrast, lithium metal anodes contain excess lithium, which effectively prevents the rapid decrease in capacity caused by lithium loss. In addition, lithium metal anodes have a high theoretical specific capacity (3860mAh g -1 ) and the lowest electrode potential (-3.04V relative to the standard hydrogen electrode), which is expected to significantly increase the energy density of lithium batteries. These characteristics make lithium metal anode the first choice for achieving high energy density low-temperature batteries.

[0003] However, the high desolvation energy under low temperature conditions poses a huge challenge to the performance of low-temperature lithium metal batteries. To this end, researchers have developed weakly solvated ether electrolytes and fluorinated electrolytes in recent years, which significantly accelerate the desolvation of Li metal batteries at low temperatures. + The desolvation kinetics of lithium metal batteries provide new ideas for the difficulty of low-temperature charging and discharging of lithium metal batteries. However, ether electrolytes generally exhibit a narrow electrochemical stability window (<4.0V), which limits their use with current high-capacity ternary cathode materials. The cost of fluorinated electrolytes has increased significantly due to the complexity of the synthesis process and the limitation of production. More importantly, the abnormal stability of the CF bond makes them highly resistant to degradation, raising concerns about their potential environmental hazards. Therefore, it is difficult for existing low-temperature electrolytes to have the characteristics of weak solvation, high voltage resistance, low cost and environmental friendliness. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a siloxane electrolyte and a preparation method thereof and application in a low-temperature lithium metal battery, aiming to solve the technical problem that the existing low-temperature electrolyte is difficult to have weak solvation, high voltage resistance, low cost and environmental friendliness.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] One of the purposes of the present invention is to provide a siloxane electrolyte, which comprises a lithium salt and dimethoxydimethylsilane, wherein the mass ratio of the lithium salt to the dimethoxydimethylsilane is 0.16-0.48:0.5-1.5.

[0007] Furthermore, the mass ratio of lithium salt to dimethoxydimethylsilane is 0.26-0.38:0.8-1.2.

[0008] Furthermore, the mass ratio of lithium salt to dimethoxydimethylsilane is 0.3-0.35:1-1.2.

[0009] Furthermore, the mass ratio of lithium salt to dimethoxydimethylsilane is 0.32:1.

[0010] Furthermore, the lithium salt is lithium bis(fluorosulfonyl)imide.

[0011] The second object of the present invention is to provide a method for preparing the above-mentioned siloxane electrolyte, comprising the following steps:

[0012] Add lithium salt to dimethoxydimethylsilane and stir at room temperature for 10 h to 15 h to obtain a siloxane electrolyte.

[0013] The third object of the present invention is to provide an application of the above-mentioned siloxane electrolyte in a low-temperature lithium metal battery, wherein the low-temperature lithium metal battery comprises a positive electrode, a negative electrode and the above-mentioned siloxane electrolyte, wherein the positive electrode and the negative electrode are arranged opposite to each other, and the siloxane electrolyte is formed between the positive electrode and the negative electrode.

[0014] Furthermore, the formation method of the siloxane electrolyte in the low-temperature lithium metal battery includes the following steps:

[0015] The siloxane electrolyte is injected between the positive electrode and the negative electrode of the low-temperature lithium metal battery, and then formed at -35℃ to -40℃ after standing.

[0016] Furthermore, the standing time is 10 hours and the formation temperature is -40°C.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The siloxane electrolyte composition provided by the present invention comprises a lithium salt and dimethoxydimethylsilane. By controlling the ratio of the lithium salt and the dimethoxydimethylsilane, a uniform and transparent solution can be formed, and good fluidity and high chemical stability can be maintained under low temperature conditions. Compared with fluorinated electrolytes, the siloxane electrolyte composition has the characteristics of low cost and environmental friendliness. The lithium salt has a strong electron-withdrawing property, which weakens the coordination effect between anions and cations in the lithium salt, making the activity of lithium ions stronger, thereby improving the ionic conductivity of the electrolyte. The silicon atoms and adjacent oxygen atoms in the dimethoxydimethylsilane solvent have a dp conjugation effect, which effectively increases the high-voltage resistance of the electrolyte and is conducive to weakening the Li + -Solvent interactions promote Li +Released during the desolvation process; in addition, the siloxane electrolyte can synergistically optimize the low-temperature bulk phase transport, interfacial chemistry and interfacial mass transfer kinetics in lithium metal batteries, giving them excellent electrochemical properties.

[0019] (2) The lithium salt of the present invention adopts lithium bis(fluorosulfonyl)imide. On the one hand, the fluorine ions in lithium bis(fluorosulfonyl)imide have strong electron-withdrawing properties, which weakens the coordination effect between anions and cations in the lithium salt, making the activity of lithium ions stronger, thereby improving the ionic conductivity of the electrolyte; on the other hand, lithium bis(fluorosulfonyl)imide has excellent electrochemical stability and can support the battery to operate in a wider operating temperature range, especially in low temperature environments, where its performance is even better. In addition, lithium bis(fluorosulfonyl)imide can also effectively passivate the positive and negative electrode interfaces, inhibit the generation of lithium dendrites at the negative electrode, and improve the high voltage resistance of the electrolyte at the positive electrode. Due to these characteristics of lithium bis(fluorosulfonyl)imide, it can improve the discharge capacity and charge and discharge times of low-temperature lithium metal batteries and extend the service life of the batteries.

[0020] (3) The siloxane electrolyte composition provided by the present invention, combined with a special low-temperature formation method, can further improve the Li + Desolvation kinetics and Li-ion transport in solid electrolyte interface (SEI) + Transport dynamics.

[0021] (4) The siloxane electrolyte provided by the present invention can match the ternary positive electrode in the low-temperature lithium metal battery and operate stably at 4.7V. After the button battery is cycled 180 times at -40°C, the capacity retention rate is 95.2%; after the 1.2Ah soft-pack battery is cycled 50 times under low temperature and poor electrolyte conditions at -20°C, the capacity retention rate is 92.1%. It has excellent low-temperature capacity retention rate and has broad application prospects in low-temperature lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a graph showing the results of the ionic conductivity test of the electrolytes of Examples 1 to 6 of the present invention.

[0023] Figure 2 It is a graph showing the test results of the ionic conductivity of the electrolytes of Example 1 and Comparative Examples 2 to 5 of the present invention.

[0024] Figure 3 The graph is a result of the ionic conductivity test of the electrolyte of Example 1 of the present invention and Comparative Example 6.

[0025] Figure 4 The long cycle capacity diagram of button cells with lithium metal and NCM811 positive electrode matched at -40°C for the electrolytes prepared in Example 1 of the present invention and Comparative Example 6.

[0026] Figure 5 It is a long cycle capacity diagram of button cells with lithium metal matched with NCM811 positive electrode at -40°C for the electrolytes of Example 1 of the present invention and Comparative Example 1.

[0027] Figure 6 The charge and discharge curves of button cells with lithium metal matched with NCM811 positive electrode at -40°C for the electrolytes of Example 1 and Comparative Example 1 of the present invention.

[0028] Figure 7 Li of the button cell of Example 1 of the present invention and Comparative Example 1 matching the lithium metal with the NCM811 positive electrode + Desolvation energy test diagram.

[0029] Figure 8 Li of the button cell of Example 1 of the present invention and Comparative Example 1 matching the lithium metal with the NCM811 positive electrode + Diagram of activation energy transfer within the SEI.

[0030] Fig. 9 This is a long cycle capacity diagram of a soft-pack battery with lithium metal matched with NCM811 positive electrode at -20°C using the siloxane electrolyte prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Certain words are used in the present invention to refer to specific components. Those skilled in the art should understand that technicians will use different nouns to refer to the same component. The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms of "a" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings.

[0033] In recent years, researchers have developed weakly solvated ether electrolytes and fluorinated electrolytes, which have significantly accelerated the development of Li +The desolvation kinetics of CF bonds provide new ideas for the difficulty of low-temperature charging and discharging of lithium metal batteries. However, ether electrolytes generally exhibit a narrow electrochemical stability window (<4.0V), which limits their use with current high-capacity ternary cathode materials. The cost of fluorinated electrolytes has increased significantly due to the complexity of the synthesis process and the limitation of production. More importantly, the abnormal stability of CF bonds makes them highly resistant to degradation, raising concerns about their potential environmental hazards.

[0034] Based on the above problems, it is of great significance to develop low-temperature electrolytes that have the characteristics of weak solvation, high voltage resistance, low cost and environmental friendliness.

[0035] Based on this, on the one hand, the present invention provides a siloxane electrolyte, which includes a lithium salt and dimethoxydimethylsilane, and the mass ratio of the lithium salt to the dimethoxydimethylsilane is 0.16-0.48:0.5-1.5.

[0036] The siloxane electrolyte composition provided by the present invention comprises a lithium salt and a dimethoxydimethylsilane solvent. On the one hand, the silicon atoms and adjacent oxygen atoms in the dimethoxydimethylsilane solvent have a dp conjugation effect, which effectively increases the high-voltage resistance of the electrolyte and is conducive to weakening the Li + -Solvent interactions promote Li + On the other hand, compared with fluorinated electrolytes, siloxane electrolytes are low-cost and environmentally friendly. The present invention provides siloxane electrolytes that can synergistically optimize low-temperature bulk phase transport, interface chemistry, and interface mass transfer kinetics in lithium metal batteries, so that they have excellent electrochemical properties; and combined with a special low-temperature formation method, it can further improve the Li of siloxane electrolytes matching low-temperature lithium metal batteries. + Desolvation kinetics and Li-ion transport in solid electrolyte interface (SEI) + Transport dynamics.

[0037] In some specific embodiments, the mass ratio of lithium salt to dimethoxydimethylsilane is 0.26-0.38:0.8-1.2. Preferably, the mass ratio of lithium salt to dimethoxydimethylsilane is 0.3-0.35:1-1.2. More preferably, the mass ratio of lithium salt to dimethoxydimethylsilane is 0.32:1. The present invention can form a uniform and transparent solution by controlling the ratio of lithium salt to dimethoxydimethylsilane, and achieve good fluidity and high chemical stability under low temperature conditions.

[0038] In some specific embodiments, the lithium salt is lithium bis(fluorosulfonyl)imide. The fluoride ions in lithium bis(fluorosulfonyl)imide have strong electron-withdrawing properties, which weaken the coordination effect between anions and cations in the lithium salt, making the activity of lithium ions stronger, thereby improving the ionic conductivity of the electrolyte. In addition, lithium bis(fluorosulfonyl)imide has excellent electrochemical stability and can support the battery to operate in a wider operating temperature range, especially in low temperature environments, where its performance is even better. In addition, lithium bis(fluorosulfonyl)imide can also effectively passivate the positive and negative electrode interfaces, inhibit the generation of lithium dendrites at the negative electrode, and improve the high voltage resistance of the electrolyte at the positive electrode. Due to these characteristics of lithium bis(fluorosulfonyl)imide, it can improve the discharge specific capacity and charge and discharge times of low-temperature lithium metal batteries and extend the service life of the batteries.

[0039] On the other hand, the present invention provides a method for preparing the above-mentioned siloxane electrolyte, comprising the following steps:

[0040] Add lithium salt to dimethoxydimethylsilane and stir at room temperature for 10 h to 15 h to obtain a siloxane electrolyte.

[0041] It should be noted that the siloxane electrolyte provided by the present invention has the following characteristics: (1) high transparency, the electrolyte salt can be completely dissolved in the electrolyte solvent; (2) good voltage resistance stability, can match the ternary positive electrode and operate stably at 4.7V; (3) high ionic conductivity, can maintain good fluidity at -40°C and match various commercial positive electrodes; (4) low cost and environmental friendliness, the cost is much lower than that of fluorinated electrolyte, and it is easy to degrade and has no risk of polluting the environment. (5) long-term stability in low-temperature operation, which can support the stable high-capacity operation of lithium metal batteries matching NCM811 positive electrodes at -20°C.

[0042] In addition, the present invention provides an application of the above-mentioned siloxane electrolyte in a low-temperature lithium metal battery, wherein the low-temperature lithium metal battery comprises a positive electrode, a negative electrode and the above-mentioned siloxane electrolyte, wherein the positive electrode and the negative electrode are arranged opposite to each other, and the siloxane electrolyte is formed between the positive electrode and the negative electrode.

[0043] It should be noted that the siloxane electrolyte provided by the present invention can synergistically optimize low-temperature bulk phase transport, interface chemistry and interface mass transfer kinetics in low-temperature lithium metal batteries, so that it has excellent electrochemical properties.

[0044] In some specific embodiments, the formation method of the siloxane electrolyte in the low-temperature lithium metal battery includes the following steps:

[0045] The siloxane electrolyte is injected between the positive electrode and the negative electrode of the low-temperature lithium metal battery, and then formed at -35℃ to -40℃ after standing.

[0046] In a specific embodiment, the standing time is 10 hours and the formation temperature is -40°C.

[0047] It should be noted that the formation method described in the present invention is specifically to complete a charge-discharge-charge at a small rate. The rate used is not specified, as long as the battery is charged and discharged normally. Among them, the temperature of room temperature formation is generally 30°C, and the SEI formed has more inorganic components, while the -35°C to -40°C formation method adopted in the present invention represents low-temperature formation, and the SEI formed has more organic components. In the siloxane electrolyte, the result of the complex interaction of multiple components in the interface region is that the lithium metal full battery matching the organic-rich SEI has faster Li+ desolvation kinetics and Li within the SEI than the inorganic-rich SEI. + Transport kinetics. Fast Li + The desolvation kinetics is attributed to the more anion-rich solvation structure in the interfacial region. + The transport kinetics is attributed to the gel-like electrolyte transport in the organic-rich SEI.

[0048] The present invention is based on the above-mentioned siloxane electrolyte, which has excellent high transparency, high electrochemical stability, high ionic conductivity, low-temperature cycle stability and other properties, and has low cost, and can make lithium-ion batteries stably operate at high capacity at -40°C to 30°C, and has broad application prospects. Siloxane electrolyte can match the ternary positive electrode in low-temperature lithium metal batteries and operate stably under 4.7V conditions. After the button battery is cycled 180 times at -40°C, the capacity retention rate is 95.2%; after the 1.2Ah soft-pack battery is cycled 50 times under low temperature and poor electrolyte conditions at -20°C, the capacity retention rate is 92.1%, which has excellent low-temperature capacity retention rate and has broad application prospects in low-temperature lithium metal batteries.

[0049] The invention is further described below through specific examples.

[0050] Example 1

[0051] This embodiment provides a siloxane electrolyte, wherein the siloxane electrolyte includes lithium bis(fluorosulfonyl)imide (LiFSI) and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.32:1.

[0052] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0053] 0.282 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0054] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0055] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0056] Example 2

[0057] This embodiment provides a siloxane electrolyte, wherein the siloxane electrolyte includes LiFSI and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.96:1.

[0058] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0059] 0.917 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0060] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0061] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0062] Example 3

[0063] This embodiment provides a siloxane electrolyte, wherein the siloxane electrolyte includes LiFSI and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.7:1.

[0064] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0065] 0.616 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0066] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0067] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0068] Example 4

[0069] This embodiment provides a siloxane electrolyte, which includes LiFSI and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.5:1.

[0070] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0071] 0.440 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0072] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0073] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0074] Example 5

[0075] This embodiment provides a siloxane electrolyte, which includes LiFSI and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.2:1.

[0076] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0077] 0.176 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0078] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0079] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0080] Example 6

[0081] This embodiment provides a siloxane electrolyte, wherein the siloxane electrolyte includes LiFSI and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.11:1.

[0082] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0083] 0.097 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0084] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0085] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0086] Comparative Example 1

[0087] This comparative example provides a siloxane electrolyte, which includes LiFSI and dimethoxydimethylsilane, and the mass ratio of LiFSI to dimethoxydimethylsilane is 0.32:1.

[0088] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0089] 0.282 g of LiFSI was added to 1 mL of dimethoxydimethylsilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0090] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0091] The siloxane electrolyte was injected between the positive electrode and the negative electrode of the lithium metal battery, and then formed at 30°C after standing.

[0092] Comparative Example 2

[0093] This comparative example provides an electrolyte, which is different from Example 1 in that ethyl silicate is selected as the electrolyte solvent, and the siloxane electrolyte includes LiFSI and ethyl silicate, and the mass ratio of LiFSI to ethyl silicate is 0.30:1.

[0094] The preparation method of the above electrolyte comprises the following steps:

[0095] 0.282 g of LiFSI was added to 1 mL of ethyl silicate and stirred at room temperature for 12 h to obtain an electrolyte solution.

[0096] The formation method of the electrolyte in the low temperature lithium metal battery includes the following steps:

[0097] The electrolyte is injected between the positive and negative electrodes of the lithium metal battery and allowed to stand at -40°C.

[0098] Comparative Example 3

[0099] This comparative example provides a siloxane electrolyte, which is different from Example 1 in that trimethylethoxysilane is selected as the electrolyte solvent. The siloxane electrolyte includes LiFSI and trimethylethoxysilane, and the mass ratio of LiFSI to trimethylethoxysilane is 0.37:1.

[0100] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0101] 0.282 g of LiFSI was added to 1 mL of trimethylethoxysilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0102] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0103] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0104] Comparative Example 4

[0105] This comparative example provides a siloxane electrolyte, which is different from Example 1 in that methyltriethoxysilane is used as the electrolyte solvent. The siloxane electrolyte includes LiFSI and methyltriethoxysilane, and the mass ratio of LiFSI to methyltriethoxysilane is 0.32:1.

[0106] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0107] 0.282 g of LiFSI was added to 1 mL of methyltriethoxysilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0108] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0109] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0110] Comparative Example 5

[0111] This comparative example provides a siloxane electrolyte, which is different from Example 1 in that dimethyldiethoxysilane is selected as the electrolyte solvent. The siloxane electrolyte includes LiFSI and dimethyldiethoxysilane, and the mass ratio of LiFSI to dimethyldiethoxysilane is 0.33:1.

[0112] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0113] 0.282 g of LiFSI was added to 1 mL of dimethyldiethoxysilane and stirred at room temperature for 12 h to obtain a siloxane electrolyte.

[0114] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0115] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0116] Comparative Example 6

[0117] This comparative example provides an ether electrolyte, which is different from Example 1 in that ethylene glycol dimethyl ether is used as the electrolyte solvent, and the siloxane electrolyte includes LiFSI and ethylene glycol dimethyl ether, and the mass ratio of LiFSI to ethylene glycol dimethyl ether is 0.33:1.

[0118] The method for preparing the above-mentioned siloxane electrolyte comprises the following steps:

[0119] 0.282 g of LiFSI was added to 1 mL of ethylene glycol dimethyl ether and stirred at room temperature for 12 h to obtain an ether electrolyte.

[0120] The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps:

[0121] The siloxane electrolyte was injected between the positive and negative electrodes of the lithium metal battery and then formed at -40°C after standing.

[0122] The electrolytes prepared in Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to an ion conductivity test, and the ion conductivity test included the following steps:

[0123] Conductivity test method: Stainless steel is used as the positive electrode and negative electrode, separated by a polytetrafluoroethylene gasket, and the electrolytes of Examples 1 to 6 and Comparative Examples 1 to 6 are added to assemble a stainless steel||stainless steel battery. The ohmic impedance of the battery is tested, and the ionic conductivity of the electrolyte is calculated by the ohmic impedance result. The results are as follows Figure 1 to Figure 3 shown.

[0124] Figure 1 The results of the ionic conductivity test of the electrolytes of Examples 1 to 6 of the present invention are shown in FIG. Figure 1 As shown, the ionic conductivity of the siloxane electrolyte used in Examples 2 to 6 is lower than that in Example 1. This shows that in the range of the mass ratio of LiFSI to dimethoxydimethylsilane of 0.16 to 0.48:0.5 to 1.5, the electrolyte with a mass ratio of LiFSI to dimethoxydimethylsilane of 0.32:1 has the highest ionic conductivity. The lithium salt concentration of the electrolyte corresponding to this mass ratio is 1.5M. High electrolyte ionic conductivity is beneficial to reducing the internal resistance of low-temperature lithium metal batteries, reducing battery polarization, and is beneficial to improving the battery discharge capacity and cycle life. Therefore, Example 1 is the most preferred siloxane electrolyte formula.

[0125] Based on this, the present invention further studies the electrolyte prepared with a mass ratio of LiFSI and dimethoxydimethylsilane of 0.32:1 in Example 1, and the results are as follows.

[0126] Figure 2 The results of the ionic conductivity test of the electrolytes of Example 1 and Comparative Examples 2 to 5 of the present invention are shown in FIG. Figure 2 As shown, at the same electrolyte concentration, the ionic conductivity of the siloxane electrolyte used in Comparative Examples 2 to 5 is lower than that of Example 1. Example 1 can maintain a conductivity greater than 10 -4 S cm -1 This ensures that the electrolyte has sufficient ion transport capacity at low temperatures, ensuring that lithium metal batteries can work normally under low temperature conditions.

[0127] Figure 3The results of the ionic conductivity test of the electrolytes of Example 1 and Comparative Example 6 of the present invention are shown in FIG. Figure 3 As shown, Example 1 has lower conductivity than the traditional ether electrolyte used in Comparative Example 6.

[0128] In order to verify that Example 1 has better low-temperature performance, the electrolytes of Example 1, Comparative Example 1 and Comparative Example 6 are assembled into a lithium metal full battery, in which the lithium sheet is used as the negative electrode and NCM811 is used as the positive electrode. The NCM811 pole piece is made by coating a mixture of NCM811 active material, conductive carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 on a carbon-coated aluminum foil to form a film, drying it in a vacuum oven at 120°C, and cutting it into a size of 12 mm in diameter to obtain an NCM811 pole piece. The electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 6 are respectively injected to assemble a button-type full battery in which lithium metal and NCM811 positive electrodes are matched.

[0129] Figure 4 The long cycle capacity diagram of the button cell with lithium metal and NCM811 positive electrode matched at -40°C for the electrolyte prepared in Example 1 of the present invention and Comparative Example 6. Figure 4 As shown, the lithium metal full battery matching Example 1 shows excellent long cycle stability and high discharge capacity characteristics under low temperature conditions. After 180 cycles at -40°C and 4.7V, the capacity retention rate is 95.2%. However, the capacity of the lithium metal full battery matching the ether electrolyte of Comparative Example 6 decays rapidly under low temperature conditions, and the charge and discharge efficiency is also very low. This is mainly due to the poor Li + Desolvation kinetics. The siloxane electrolyte in Example 1 has dp conjugated effect between silicon atoms and adjacent oxygen atoms, which makes Li + -Solvent interactions weakened, accelerating the Li + Desolvation kinetics.

[0130] In order to verify the effect of the formation method on the low-temperature performance of the siloxane electrolyte, Example 1 and Comparative Example 1 were subjected to low-temperature charge and discharge cycle tests of a low-temperature lithium metal full battery. Figure 5 The long cycle capacity diagram of the button cell with lithium metal and NCM811 positive electrode matched at -40°C for the electrolyte of Example 1 and Comparative Example 1 of the present invention. Figure 5 As shown, although the same electrolyte is matched, the capacity of the lithium metal full battery formed at low temperature in Example 1 is higher than the sample data of the low temperature formed in Comparative Example 1. This shows that low temperature formation can form an interface layer with faster interface transport kinetics.

[0131] Figure 6 The charge and discharge curves of the button cell with lithium metal and NCM811 positive electrode matched at -40°C for the electrolyte of Example 1 and Comparative Example 1 of the present invention are shown in FIG. Figure 6As shown, the charge and discharge prove that the comparative example 1 has a higher polarization than the example 1, which indicates that the sample formed at room temperature will have a larger interface impedance.

[0132] Figure 7 Li of the button cell of Example 1 of the present invention and Comparative Example 1 matching the lithium metal with the NCM811 positive electrode + Desolvation energy test diagram. Figure 8 Li of the button cell of Example 1 of the present invention and Comparative Example 1 matching the lithium metal with the NCM811 positive electrode + Transmission activation energy test diagram within SEI. Figure 7-8 As shown, the Li of Comparative Example 1 and Example 1 were tested respectively. + Desolvation energy and Li in SEI + The results show that the samples formed at low temperature have lower desolvation energy and activation energy of transport within SEI, which once again verifies that low temperature formation can form an interfacial layer with faster interfacial transport kinetics.

[0133] The present invention conducts a comprehensive performance test on the electrolyte prepared in Example 1. Fig. 9 This is a long cycle capacity diagram of a soft-pack battery with lithium metal and NCM811 positive electrode matched at -20°C using the siloxane electrolyte prepared in Example 1 of the present invention. Fig. 9 The electrolyte used in Example 1 at -20°C, the 1.2Ah soft pack battery with lithium metal and NCM811 positive electrode matched shows excellent long cycle stability and high discharge capacity characteristics under low temperature and poor electrolyte conditions, with a capacity retention rate of 92.1% within the low temperature test range of 50 cycles, and an average charge and discharge efficiency of up to 99.7%.

[0134] As can be seen from the above, the siloxane electrolyte provided by the present invention includes lithium bis(fluorosulfonyl)imide and dimethoxydimethylsilane. By controlling the ratio of lithium bis(fluorosulfonyl)imide and dimethoxydimethylsilane, a uniform and transparent solution can be formed, and good fluidity and high chemical stability can be maintained under low temperature conditions. The silicon atom and the adjacent oxygen atom in the dimethoxydimethylsilane have a dp conjugated effect, which effectively increases the high-voltage resistance of the electrolyte and is conducive to weakening the Li + -Solvent interaction promotes the release of lithium ions during the desolvation process; combined with the low-temperature formation method, it can significantly improve the electrochemical performance of lithium batteries in the low-temperature range, can match the ternary positive electrode and operate stably at 4.7V, and has excellent low-temperature capacity retention rate (after 180 cycles of button batteries at -40°C, the capacity retention rate is 95.2%; after 50 cycles of 1.2Ah soft-pack batteries at -20°C under low temperature and lean electrolyte conditions, the capacity retention rate is 92.1%), and has broad application prospects in low-temperature lithium metal batteries.

[0135] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0136] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A siloxane electrolyte, characterized in that: The siloxane electrolyte comprises lithium salt and dimethoxydimethylsilane, and the mass ratio of the lithium salt to the dimethoxydimethylsilane is 0.16-0.48:0.5-1.

5.

2. The siloxane electrolyte according to claim 1, characterized in that: The mass ratio of lithium salt to dimethoxydimethylsilane is 0.26-0.38:0.8-1.

2.

3. The siloxane electrolyte according to claim 1, characterized in that The mass ratio of lithium salt to dimethoxydimethylsilane is 0.3-0.35:1-1.

2.

4. The siloxane electrolyte according to claim 1, characterized in that: The mass ratio of lithium salt to dimethoxydimethylsilane is 0.32:

1.

5. The siloxane electrolyte according to claim 1, characterized in that: The lithium salt is lithium bis(fluorosulfonyl)imide.

6. A method for preparing a siloxane electrolyte according to any one of claims 1 to 5, characterized in that: The following steps are involved: Add lithium salt to dimethoxydimethylsilane and stir at room temperature for 10 h to 15 h to obtain a siloxane electrolyte.

7. Use of the siloxane electrolyte according to any one of claims 1 to 5 in a low-temperature lithium metal battery, characterized in that: The low-temperature lithium metal battery comprises a positive electrode, a negative electrode and the siloxane electrolyte according to any one of claims 1 to 5, the positive electrode and the negative electrode are arranged opposite to each other, and the siloxane electrolyte is formed between the positive electrode and the negative electrode.

8. The use according to claim 7, characterized in that: The formation method of siloxane electrolyte in low temperature lithium metal battery includes the following steps: The siloxane electrolyte is injected between the positive electrode and the negative electrode of the low-temperature lithium metal battery, and then formed at -35℃ to -40℃ after standing.

9. The use according to claim 8, characterized in that: The standing time is 10 hours, and the forming temperature is -40°C.

Citation Information

Patent Citations

  • Electrolyte for stabilizing silicon-carbon surface of lithium ion battery and preparation method thereof, and application of electrolyte for stabilizing silicon-carbon surface of lithium ion battery

    CN110190331A

  • Electrolyte for lithium ion battery, lithium ion battery and vehicle

    CN116742136A

  • Local high-concentration electrolyte, preparation method thereof and battery

    CN116960465A

  • Low-temperature low-density sodium ion battery electrolyte and sodium ion battery

    CN117810542A

  • Stabilized lithium electrochemical cells containing an alkoxy silane

    US6416906B1

Cited By

  • Multi-component synergistic siloxane electrolyte system and SEI membrane in-situ construction method

    CN121726537A